Varieties of Open Governance: How Openness Projects Organize and Make Decisions. (13th September 2016) - Ingrams, Alex
Abstract : Related Content:Balfour and Newbold (PAR November/December 2016) Related Content:King (PAR November/December 2016) Related Content:Fiorino (PAR November/December 2016) Related Content:Knox (PAR November/December 2016) Related Content:Brook (PAR November/December 2016)